Nutritional status of under six years old children in Kalar city, Kurdistan Region, Iraq - Hawal Lateef Fateh; Mostafa Nachvak; Hadi Abdollahzad; Shahab Rezaeian; Mina Darand; Amir Bagheri (BMC, 2022)
Abstract Introduction Nutritional problems in children cause major morbidity and mortality in the world. This study aimed to assess the nutritional status of under six years old children in Kalar city, Kurdistan Region, Iraq. Methods In this longitudinal study, data from 403 Iraqi Kurdish children aged 0-72 months and their mothers were extracted from Health Centre in Kalar city undertaken between 2013 and 2019. The children`s growth data were obtained at birth time, 6, 12, 24, and 72 months. Epi Info was used to classify the children of nutritional status by converting the anthropometric measurements into Z-scores. Data were analyzed using SPSS 25 software. Results The prevalence of overweight and obesity rose from birth to age 6 years old, from 19.6% and 7.4% to 52.2% and 30.5%, respectively. At 24 month, children had the highest rates of being overweight (56.1%) and obesity (34%). At 6 month, the highest prevalence of wasting exists (9.5%). At 6 month boys and girls had the highest frequency of stunting, 17.2% and 7.2% respectively. Considering the association of all characteristic variables and growth data at birth time, only mothers with academic education had children with significantly higher BMI for age compared to illiterate mothers after adjusting for all potential confounders (β: 0.573, 95% CI: 0.105, 1.04, P: 0.017). Conclusion The study suggests that some analysed factors that accounted for malnutrition in Kalar city's children are preventable. Therefore, to reduce the burden of malnutrition, community-based education and targeted nutritional interventions are required.